Osteopontin/SPP1: a potential mediator between immune cells and vascular calcification - Zhao, Yanli; Huang, Zujuan; Gao, Limei; Ma, Hongbo; Chang, Rong (Frontiers in Immunology, 2024)
Vascular calcification (VC) is considered a common pathological process in various vascular diseases. Accumulating studies have confirmed that vascular calcification is involved in the inflammatory response in heart disease, and SPP1+ macrophages play an important role in this process. In vascular calcification, studies have focused on the physiological and pathological functions of macrophages, such as pro-inflammatory or anti-inflammatory cytokines and pro-fibrotic vesicles. Additionally, macrophages and activated lymphocytes highly express SPP1 in atherosclerotic plaques, which promote the formation of fatty streaks and plaque development, and SPP1 is also involved in the calcification process of atherosclerotic plaques that results in heart failure, but the crosstalk between SPP1-mediated immune cells and vascular calcification has not been adequately addressed. In this review, we summarize the regulatory effect of SPP1 on vascular calcification in T cells, macrophages and dendritic cells in different organs' vascular calcification, which could be a potential therapeutic target for vascular calcification.